2021
DOI: 10.1159/000520040
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Aα Contributes to IgE-Dependent Mast-Cell Mediator Secretion in Allergic Inflammation

Abstract: Mast cells (MCs) are key mediators of allergic inflammation through the activation of cross-linked immunoglobulin E (IgE) bound to the high-affinity IgE receptor (FcϵRI) on the cell surface, leading to the release of biologically potent mediators, either from preformed granules or newly synthesized. Pharmacological inhibitors have been developed to target a key signaling protein phosphatase in this pathway, calcineurin, yet there is a lack of genetic and definitive evidence for the various isoforms of calcineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…7 A recent study in mice suggested that calcineurin subunit A (CnAα) is involved in the early phases of mast cell-driven allergy reactions, and its de ciency resulted in the decrease of degranulation and in ammatory cytokines secretion in allergic responses. 22 According to these studies, we hypothesize that CsA may be effective against ACDE.…”
Section: Discussionmentioning
confidence: 96%
“…7 A recent study in mice suggested that calcineurin subunit A (CnAα) is involved in the early phases of mast cell-driven allergy reactions, and its de ciency resulted in the decrease of degranulation and in ammatory cytokines secretion in allergic responses. 22 According to these studies, we hypothesize that CsA may be effective against ACDE.…”
Section: Discussionmentioning
confidence: 96%
“…Many components involved in this process heavily rely on the intracellular calcium concentrations that are refilled by the efflux of ER calcium and influx of extracellular calcium. For example, calcineurin Aα that contributes to the release of allergic mediators in activated mast cells is calcium-dependent [71]. The calcium sensor, cation channels, and calcium-binding proteins (e.g., S100) are all involved in maintaining the intracellular calcium concentrations (Fig.…”
Section: Intracellular Signaling Transduction In Mast Cellsmentioning
confidence: 99%